A Fire of Lilies Perspectives on Literature and Politics in Modern Iran - Karimi-Hakkak, Ahmad (Iranian Studies Series, 2019)
This book examines the role of Persian literature in politics in the tumultuous period of Iranian history from 1950 to 2000, illustrating how intellectuals used poetry, plays, novels and short stories to comment on socio-political developments. The unique aspect of the book is its strong empirical perspective as it analyses how Persian intellectuals dealt with sensor, suppression, imprisonment, exile and even execution for the sake of expression of free speech. Karimi-Hakkak's methodology is also unique as he applies theoretical perspectives of various disciplines to produce a multi-faceted work, which provide the reader with a concise socio-political history based on the interaction between literature and politics.'A Fire of Lilies' will therefore make a significant contribution to the research on modern Persian literature as well as literary historiography.